PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA PT SOCFIN INDONESIA - Fitri Ayu Lestari; Indra Fauzi (Universitas Dharmawangsa, 2023)
This study aims to determine the effect of the use of information technology and human resource competence on the effectiveness of accounting information systems at PT Socfin Indonesia. This type of research is descriptive quantitative. The population in this study were all employees of PT Socfindo with a total of 394 employees. The sample used in this study was purposive sampling with a total sample of 30 employees at PT Socfin Indonesia. The data collection method in this study uses primary data. By collecting data through observation, documentation, and questionnaires (Questionnaire). In this study using the validity test, reliability, descriptive analysis test, multiple linear regression analysis, classical assumption test, test the coefficient of determinant (R2) and hypothesis testing with the help of the SPSS 21 program. With the test results in each variable there is a positive and significant influence on system effectiveness Accounting Information. And from the results of the determination test of 0.963 or 96.3%, which shows that there is a simultaneous influence between variables X1 and X2 on variable Y of 96.3% and the rest is influenced by other variables.